Air Pollution Control Policies in China: A Retrospective and Prospects. - Yana Jin; Andersson, Henrik; Zhang, Shiqiu (Int J Environ Res Public Health, 2016)
With China's significant role on pollution emissions and related health damage, deep and up-to-date understanding of China's air pollution policies is of worldwide relevance. Based on scientific evidence for the evolution of air pollution and the institutional background of environmental governance in China, we examine the development of air pollution control policies from the 1980s and onwards. We show that: (1) The early policies, until 2005, were ineffective at reducing emissions; (2) During 2006-2012, new instruments which interact with political incentives were introduced in the 11th Five-Year Plan, and the national goal of reducing total sulfur dioxide (SO₂) emissions by 10% was achieved. However, regional compound air pollution problems dominated by fine particulate matter (PM) and ground level ozone (O₃) emerged and worsened; (3) After the winter-long PM episode in eastern China in 2013, air pollution control policies have been experiencing significant changes on multiple fronts. In this work we analyze the different policy changes, the drivers of changes and key factors influencing the effectiveness of policies in these three stages. Lessons derived from the policy evolution have implications for future studies, as well as further reforming the management scheme towards air quality and health risk oriented directions.
Keywords: Air Pollutants; air pollution; China; Environmental Monitoring; Environmental Policy; Environmental Pollution; Humans; Particle size; particulate matter; Retrospective Studies